STRATEGI PENGEMBANGAN OBJEK WISATA KONSERVASI PENYU AMPING PARAK KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - zizi, salma putri (JURNAL BUANA, 2025)
This study aims to Strategy for the Development of Turtle Conservation Tourism Objects in Kenagarian Amping Parak, Sutera District, Pesisir Selatan Regency. The technique used at the time of data collection was by interviewing several sources, observations, questionnaires, documentation and triangulation. The sources used were primary data and secondary data. This research technique used Miles & Huberman analysis to analyze attraction, and site analysis for planning. The results of the study show the development of the characteristics of turtle conservation tourism objects, based on the results of turtle conservation research, there is a lack of facilities and infrastructure for the development strategy of turtle conservation. This is very good, it can be seen from the huge opportunity to be used as an educational tour for all circles.